Comparison of ÃÂ²-Hydroxylase Enzyme 11 Serum in Obese, Overweight, and Normoweight Young Men - Sitepu, Jenny Novina; Sari, Mutiara Indah; Tann, Gino (Indonesian Journal of Medicine, 2016)
Background: Previous studies showed that cardiovascular risk factor was increased in obese and overweight subjects. Obesity and cardiovascular risk factor are associated with hypothalamic-pituitary-adrenal (HPA) axis hyperactivity that causes hypercortisolism, cortisol level is associated with cardiovascular risk factor on obesity. 11 ÃÂ²-hydroxylase is an enzyme that involved in cortisol synthesis. The aim of this study was to investigate 11 ÃÂ²-Hydroxylase concentration in obesity, overweight, and normal weight young men.Subjects and Method: This was analytic-observational study using cross-sectional design. The study was conducted at HKBP Nommensen University, Medan. The study subjects included by 76 young men aged 18-28 years old, consisting of 25 obese subjects, 25 overweight, and 25 normoweight. The concentration of 11 ÃÂ²-Hydroxylase was evaluated in blood sample after 10 hours fasting. The data was analyzed bivariately.Results: Mean of 11 ÃÂ²-Hydroxylase concentration was 52.76 ÃÂ± 44.27 in obese subjects, 70.16 ÃÂ± 46.83 in overweight subjects, and 43.42 ÃÂ± 27.75 in normoweight subjects. The 11 ÃÂ²-Hydroxylase concentration in overweight subjects was statistically higher than normoweight subjects (p = 0.007), but the 11 ÃÂ²-Hydroxylase concentration on obese subjects statistically was not different from normoweight subjects (p = 0.362).Conclusion: The 11 ÃÂ²-Hydroxylase concentration on overweight subject is higher than normoweight subject. There is no difference of 11 ÃÂ²-Hydroxylase concentration on obese and normoweight subject. Mitochondrial stress and mitochondrial failure mechanism on overweight and obesity merit further investigation.Keywords: 11 ÃÂ²-Hydroxylase, cortisol, obesity, overweightCorrespondence:ÃÂ Jenny Novina Sitepu. Faculty of Medicine, HKBP Nommensen Medan University, Medan.Indonesian Journal of Medicine (2016), 1(1): 71-75https://doi.org/10.26911/theijmed.2016.01.01.09